2014
DOI: 10.1016/j.apenergy.2014.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic analysis of ammonia production via integrated biomass gasification

Abstract: Ammonia (NH 3) can be produced by synthesis of nitrogen and hydrogen in the Haber-Bosch process, where one of the challenges is the availability of a sustainable and economic hydrogen source. Natural gas is currently the main feedstock for NH 3 production and a more environmentally sustainable alternative could be the use of biomass-based synthesis gas. The main objective of this paper is to perform a techno-economical evaluation of the production of biomass-based NH 3 from the integration of a pressurized ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(73 citation statements)
references
References 15 publications
0
65
0
1
Order By: Relevance
“…Ammonia production via integrated biomass gasification was studied by Andersson and Lundgren [14]. The process simulator was used to model energy and material balances of the complete biomass gasification system including the NH 3 synthesis.…”
Section: Ammonia Synthesismentioning
confidence: 99%
“…Ammonia production via integrated biomass gasification was studied by Andersson and Lundgren [14]. The process simulator was used to model energy and material balances of the complete biomass gasification system including the NH 3 synthesis.…”
Section: Ammonia Synthesismentioning
confidence: 99%
“…At this stage, wheat straw is first dried in a rotary dryer heated indirectly to decrease its moisture content and subsequently ground into acceptable small particles . In this study, the specific work required for biomass drying is assumed to be 15 kW h per wet tonne to reach the desired biomass moisture content of 7 wt %. However, the energy penalty related to the grinding of biomass particles to obtain an average biomass size of 0.6–0.8 mm accounts for 3 % of the biomass thermal input…”
Section: Process Design and Modelingmentioning
confidence: 99%
“…To obtain ah igh carbon conversion and ah igh biosyngas quality,t he pretreatment of biomass is necessary.A tt his stage,w heat straw is first dried in ar otary dryer heated indirectly to decrease its moisture content and subsequently ground into acceptable small particles. [28] In this study,t he specific work required for biomass drying is assumed to be 15 kW hp er wet tonne [29] to reach the desired biomass moisture content of 7wt%.H owever, the energy penalty related to the grinding of biomass particles to obtain an average biomass size of 0.6-0.8 mm accounts for 3% of the biomass thermal input. [30] Ty pically,a tl east three representative reactors for biomass gasification are used, that is,af ixed-bedg asifier, as ingle or circulating fluid-bed gasifier, and an entrainedbed gasifier.…”
Section: Biomass Gasificationmentioning
confidence: 99%
“…Process integration studies of various thermochemical biorefinery concepts at different industrial sites have been reported in the literature, such as at a biomass-fired combined heat and power plant (Heyne et al, 2012); pulp and paper mills (Andersson and Lundgren, 2014;Consonni et al, 2009); a mechanical pulp and paper mill co-located with a sawmill plant (Isaksson et al, 2012); a steel plant (Johansson, 2013;Lundgren et al, 2013); a chemical cluster (Holmgren et al, 2014); and oil refineries (Brau et al, 2013;Johansson et al, 2012;Sadhukhan and Ng, 2011). Oxo synthesis is another possible interesting application of biomass-derived syngas (Boerrigter and Rauch, 2006;Spath and Dayton, 2003).…”
Section: Introductionmentioning
confidence: 99%